2018
DOI: 10.1038/s41598-018-23997-w
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the polyadenylation factor EhCFIm25 with RNA aptamers controls survival in Entamoeba histolytica

Abstract: Messenger RNA 3′-end polyadenylation is an important regulator of gene expression in eukaryotic cells. In our search for new ways of treating parasitic infectious diseases, we looked at whether or not alterations in polyadenylation might control the survival of Entamoeba histolytica (the agent of amoebiasis in humans). We used molecular biology and computational tools to characterize the mRNA cleavage factor EhCFIm25, which is essential for polyadenylation in E. histolytica. By using a strategy based on the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 69 publications
1
17
0
2
Order By: Relevance
“…Interestingly, the absence of certain conserved residues in the Nudix domain does not significantly affect the folding neither the RNA binding of CFIm25 in E. histolytica (Ospina‐Villa et al. ,b; Pezet‐Valdez et al. ), highlighting the relevance of the domain folding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the absence of certain conserved residues in the Nudix domain does not significantly affect the folding neither the RNA binding of CFIm25 in E. histolytica (Ospina‐Villa et al. ,b; Pezet‐Valdez et al. ), highlighting the relevance of the domain folding.…”
Section: Discussionmentioning
confidence: 99%
“…; Ospina‐Villa et al. ,b; Zamorano et al. ) and the conservation of the polyadenylation process through the evolutionary scale, we proposed a refined model in which the EhCPSF complex binds the consensus poly(A) signal UA(A/U)UU through the EhWDR33 polypeptide, while EhCstF complex recognizes the U‐rich motif downstream the poly(A) site, tethering other factors to RNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the absence of a classical RBD, EhCFIm25 is able to bind the 3′ UTR of E. histolytica transcripts and this interaction involves the participation of the conserved Leu135 and Tyr236 residues (Ospina-Villa et al, 2015 ). EhCFIm25 recognizes the GUUG motif in mRNA 3′end, while the human protein binds the UGUA sequence; consequently, aptamers containing this motif specifically identify the parasite protein, suggesting that they could be used as molecular tools for diagnosis or therapeutic purposes (Ospina-Villa et al, 2018 ). Interestingly, EhCFIm25 interacts with EhPAP (Pezet-Valdez et al, 2013 ), which indicates that it may be introduced into the processing complex in the early steps of the cleavage/polyadenylation reaction.…”
Section: Understanding Polyadenylation In E Histolyticamentioning
confidence: 99%
“…Interestingly, EhCFIm25 interacts with EhPAP (Pezet-Valdez et al, 2013 ), which indicates that it may be introduced into the processing complex in the early steps of the cleavage/polyadenylation reaction. EhCFIm25 controls the selection of the distal poly(A) site during mRNA 3′ end formation; consequently, its silencing by dsRNA or its blocking by aptamers alter parasite proliferation and virulence, demonstrating for the first time the relevance of polyadenylation factors as biochemical targets in E. histolytica (Ospina-Villa et al, 2017 , 2018 ). Other works have also recently reported that targeting polyadenylation factors represents a valuable strategy for the control of the protozoan parasites Trypanosoma brucei (CPSF-30), Toxoplama gondii , and Plasmodium falciparum (CPSF-73) (Hendriks et al, 2003 ; Sidik et al, 2016 ; Palencia et al, 2017 ; Sonoiki et al, 2017 ).…”
Section: Understanding Polyadenylation In E Histolyticamentioning
confidence: 99%